Media Production Lab - architecture as urban stage [Tshwane University of Technology Departments of Journalism and Public Relations in the faculty of Humanities] : a classroom for socio-cultural spirit and expression - White, G.T. (Gary) (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2010.